2013
DOI: 10.1159/000353365
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Cardiac Arrest in Acute Coronary Syndromes: Insights from the Global Registry of Acute Coronary Events and the Canadian Registry of Acute Coronary Events

Abstract: Objectives: Cardiac arrest in acute coronary syndromes (ACS) is associated with high morbidity and mortality. We examined the clinical characteristics, contemporary management patterns and outcomes of ACS patients with pre-hospital cardiac arrest. Methods: The Global Registry of Acute Coronary Events and the Canadian Registry of Acute Coronary Events enrolled 14,010 ACS patients in 1999-2008. We compared the clinical characteristics, in-hospital treatment and outcomes between patients with and without pre-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…In contrast, ASA does inhibit the production of both compounds directly by inhibiting cyclooxygenase 1 [ 25 28 ]. Our findings were consistent with this expectation, and supported by an experimental study which showed that clopidogrel pre-treatment did not reduce ischemia-induced VF incidence [ 20 ], and a clinical report that, among patients with acute coronary syndrome, clopidogrel use was not different between those with or without pre-hospital cardiac arrest [ 24 ]. We observed an increased risk of OHCA in the setting of AMI upon use of clopidogrel.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, ASA does inhibit the production of both compounds directly by inhibiting cyclooxygenase 1 [ 25 28 ]. Our findings were consistent with this expectation, and supported by an experimental study which showed that clopidogrel pre-treatment did not reduce ischemia-induced VF incidence [ 20 ], and a clinical report that, among patients with acute coronary syndrome, clopidogrel use was not different between those with or without pre-hospital cardiac arrest [ 24 ]. We observed an increased risk of OHCA in the setting of AMI upon use of clopidogrel.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with our findings which demonstrated reduced OHCA risk in the setting of AMI upon ASA use. Moreover, a study among patients with acute coronary syndrome found that patients who suffered pre-hospital cardiac arrest (without VT/VF documentation) were less frequently treated with ASA than patients without pre-hospital cardiac arrest [ 24 ]. However, the exposure window of ASA in that study was defined as the use of ASA prior to hospital presentation, which carries the risk of misclassification of ASA use by including past users (rather than current users) in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons should be made only between similar hospitals and in selected, well-defined, high-risk-specific populations with prognosis known to be dependent on overall cardiology management (Groups of Related Diagnosis or GRDs). 39 , 53–55 Extreme high-risk and low-prevalence groups of patients should be excluded from analysis rather than corrected for risk. 53 , 54 Sometimes this information is not well reflected in registries or databases, stressing the importance of dedicated databases for the measurement of quality outcomes.…”
Section: Adjustment Of Outcomes Metricsmentioning
confidence: 99%
“…39 , 53–55 Extreme high-risk and low-prevalence groups of patients should be excluded from analysis rather than corrected for risk. 53 , 54 Sometimes this information is not well reflected in registries or databases, stressing the importance of dedicated databases for the measurement of quality outcomes. 54 Table 3 shows the recommended populations for benchmarking.…”
Section: Adjustment Of Outcomes Metricsmentioning
confidence: 99%
“…In the chain of survival, early defibrillation is a strong predictor of survival in OHCA patients with shockable rhythm [9]. Shockable rhythm is known to have a higher survival rate and higher association with acute coronary syndrome than non-shockable rhythm, with better chance of return of spontaneous circulation (ROSC) [10]. Among OHCA patients who were transported to the hospital by emergency medical technicians (EMTs), initial shockable rhythms accounted for approximately 22.9% of cases in the USA and 18.8% of cases in Taiwan in the control group [1,11].…”
Section: Introductionmentioning
confidence: 99%